Almacenamiento de carbono y análisis de rentabilidad en sistemas agroforestales con Coffea arabica (L.) en la zona de los Santos, Costa Rica - Castro-Solís, Roberto José (Instituto Tecnológico de Costa Rica, 2017)
Coffee cultivation is one of the most important agricultural products nationwide. The Santos area is a coffee region that stands out for its high quality coffee, however, the action of climate change and inadequate management practices put their production at risk. Given this situation, the incorporation of trees in the coffee plantations emerges as a very interesting alternative, since they have the possibility of generating products and financial, environmental and social benefits that improve the sustainability of the system. The general objective of this thesis is to determine which arrangement presents the greatest integral benefits within an agroforestry system in the Zona de los Santos. The evaluated arrangements were coffee-Persea americana, coffee-Grevillea robusta, coffee-Erythrina sp. and coffee-Full sun. Through a completely randomized design and a financial analysis, it was determined which combination stored the most carbon in the system and which arrangement was the most profitable
Proyecto de Graduación (Licenciatura en Ingeniería Forestal) Instituto Tecnológico de Costa Rica, Escuela de Ingeniería Forestal, 2017.
Keywords: Café; Rentabilidad; Sistemas agroforestales; Productos agrícolas; Calidad; Producción; Sostenibilidad